Perlindungan Hukum Bagi Pemegang Lisensi Game Online Di Banten Berdasarkan Undang-Undang Nomor 28 Tahun 2014 Tentang Hak Cipta - Tri Dodi Setyawan (JOURNAL of LEGAL RESEARCH, 2021)
This study discusses the legal protection afforded to licensees against the act of pirating online games, as well as the legal remedies available to licensees.This research is expected to be useful as input for writers or other parties interested in analyzing legal protection for licensees. The normative juridical literature research method was used in this study, namely research that refers to legal norms found in the law, literature, expert opinion, and journals. According to the study's findings, there are legal remedies available to online game licensees in the event of piracy, including both litigation and non-litigation, and it can also be stated that in criminal cases of theft, it can be said to be theft due to taking rights that do not belong to Islamic law, namely the accusation of theft (sariqah).